Determination of Fe, Zn and Cu in ambient air by Combining pre-concentration Methods and FAAS - Yaman, M.; Erel, E. (Univ Tehran, 2013)
The main sources of human exposure to trace metals for non-occupationally exposed individuals are inhalation and ingestion. Because the absorption rates of the metals by inhalation are significantly higher. (up to 50-60%) than those by ingestion (between 3% and 10%), determination of trace metals in ambient air samples is of special interest The main purpose of this study was to determine Fe, Zn and Cu in ambient air by combining pre-concentration methods and flame atomic absorption spectrophotometer (FAAS). In the pre-concentration step, adsorption reagents including 4-(2-pyridyl-azo) Resorcinol (PAR)-loaded XAD-7, thioureasulphonamide polymeric resin and cupferron-activated carbon were used sequentially. Under the optimum conditions, seasonal distributions of Fe, Zn and Cu concentrations in ambient air of Elazig City, Turkey, were determined. Concentrations of Fe, Zn and Cu were found to be in the ranges of 154-416, 101-323 and 12-75 ng/m(3), respectively. High Zn levels determined in March and April can be attributed to the burning of coal at the beginning of spring.
Keywords: Air; Metals; Pre-concentration; AAS; Atmosphere